Review of acoustic comfort evaluation in dwellings: Part III—airborne sound data associated with subjective responses in laboratory tests. Issue 4 (December 2018) - Vardaxis, Nikolaos-Georgios; Bard, Delphine
Acoustic comfort has been used in engineering to refer to conditions of low noise levels or annoyance, while current standardized methods for airborne and impact sound reduction are used to assess acoustic comfort in dwellings. However, the results and descriptors acquired from acoustic measurements do not represent the human perception of sound or comfort levels. This article is a review of laboratory studies concerning airborne sound in dwellings. Specifically, this review presents studies that approach acoustic comfort via the association of objective and subjective data in laboratory listening tests, combining airborne sound acoustic data, and subjective ratings. The presented studies are tabulated and evaluated using Bradford Hill's criteria. Many of them attempt to predict subjective noise annoyance and find the best single number quantity for that reason. The results indicate that subjective response to airborne sound is complicated and varies according to different sound stimuli. It can be associated sufficiently with airborne sound in general but different descriptors relate best to music sounds or speech stimuli. The inclusion of low frequencies down to 50 Hz in the measurements seems to weaken the association of self-reported responses to airborne sound types except for the cases of music stimuli.